2022
DOI: 10.1155/2022/4592986
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of ET-1 in Early Cerebral Microcirculation Changes after Subarachnoid Hemorrhage

Abstract: Subarachnoid hemorrhage (SAH), especially aneurysmal subarachnoid hemorrhage, is a serious cerebrovascular disease with high mortality and morbidity. However, there is no effective treatment in clinics. In recent years, more and more studies have shown that early brain injury (EBI) may be an important reason for poor prognosis of SAH. Explore the mechanism of early brain injury after subarachnoid hemorrhage (SAH). In this study, 20 male New Zealand white rabbits were selected and divided into the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A few studies demonstrated that circulating high mobility group box-1 (HMGB-1) increases during acute SAH and blocking HMGB-1 using monoclonal antibodies confers protective functions [127,128]. Some experimental studies observed elevated serum cytokines (MMP-9, IL-1β, and IL-6) and increased inflammatory mediators (TNFα, IL-6, IL-2, and CCL2) post-SAH [129][130][131]. Similar results were observed in SAH patients, where MMP-9 and IL-6 levels were elevated post-SAH, and the serum levels of MMP-9 and IL-6 were associated with the severity and poor prognosis of SAH [132].…”
Section: Clinical Potential Of Immunotherapies In Shtmentioning
confidence: 99%
“…A few studies demonstrated that circulating high mobility group box-1 (HMGB-1) increases during acute SAH and blocking HMGB-1 using monoclonal antibodies confers protective functions [127,128]. Some experimental studies observed elevated serum cytokines (MMP-9, IL-1β, and IL-6) and increased inflammatory mediators (TNFα, IL-6, IL-2, and CCL2) post-SAH [129][130][131]. Similar results were observed in SAH patients, where MMP-9 and IL-6 levels were elevated post-SAH, and the serum levels of MMP-9 and IL-6 were associated with the severity and poor prognosis of SAH [132].…”
Section: Clinical Potential Of Immunotherapies In Shtmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%